Water quality and nutrient loading in the coastal waters of Boracay Island, Malay., Aklan, Central Philippines - Limates, Vilma G. (2016)
This study analyzed the water quality in the coastal zone of Boracay Island in relation to anthropogenic activities and natural factors. Seven sites were studied where possible sources of nutrient inputs on spatial and temporal basis were identified. Water samples were evaluated using the Philippine Department of Environment and Natural Resources (DENR) regulatory standards. The coastal water quality was generally influenced loading coming from untreated and partially treated waste water from households and commercial establishments not connected to the sewerage system of the island. Natural cleansing mechanisms attributed to activities of autotrophs in the coastal water and biogeochemical processes of mangrove swamps are operational. Coastal waters adjacent to mangrove swamp with relatively good mangrove cover exhibited good water quality. The months of February to June with highest number of tourist arrival proved to be the critical area in the Island. Puka Beach close to Mangove Swamp 1with good mangrove cover showed the cleanest water quality, followed by Long Beach with most of the commercial establishments connected to the sewerage system.
Keywords: Quality of Water; Water quality management